The Consumption of Premium Coffee-The Influence of Hedonic Needs vs. Utilitarian Needs - Hew, Keat Loong (2013)
The paper looks at the influence that hedonic and utilitarian needs exude on consumer’s preference for premium coffee and ultimately their willingness to pay a premium for the coffee. Utilitarian needs are related to a desire to achieve some functional or practical benefit and often linked with the notion of product performance and usefulness (e.g. drinking coffee to accomplish a specific task such as a need to stay alert due to work requirement). It has tangible and actual attributes where consumers follow utility and maximizing approach. Hedonic needs are more subjective and emotional (intangible), and results more from fun and entertainment than from task completion (e.g. drinking coffee to satisfy need for affiliation & socialisation, or drinking coffee at a certain outlet reminded one of a vacation e.g. a café that resembles a Parisian café or Italian bistro). They are typically non-instrumental, experiential and affective. A quantitative research is employed for the study due to its objectivity and formal systematic process for analysing the research questions from the numerical data gathered from the surveys. An online survey is used to gather respondents feedback on their premium coffee consumption. A mixture of open-ended questions, rank questions and Likert-scale questions are used to gather respondents’ feedback. In summary, the findings seem to imply that consumers’ preference for premium coffee are driven mostly by utilitarian needs; with the consistent taste and quality of the coffee being the most important attributes. Ambience plays a key role in influencing consumers’ utilitarian choice, with the convenient location and cleanliness appearing to be basic conditional requirements influencing the choice of place to purchase the coffee. In general, consumers are undecided and reluctant to pay premium for their coffee at a price point of RM10 and more. Though consumers’ willingness to pay a higher price for premium coffee is not conclusive, the influence of the coffee beans quality (which has a primary effect in influencing the taste of the coffee) and the drink variety and customization to one’s preference are exhibited.